Effects of sleep-disordered breathing and hypertension on cognitive function in elderly adults. (2nd April 2020) - Kato, Kazuko; Noda, Akiko; Yasuma, Fumihiko; Matsubara, Yuka; Miyata, Seiko; Iwamoto, Kunihiro; Miyazaki, Soichiro; Ozaki, Norio
ABSTRACT: Purpose : The prevalence of sleep-disordered breathing (SDB) increases with aging. SDB is a risk of hypertension, and both might lead to cognitive decline. However, the role of SDB and hypertension on the pathogenesis of age-related cognitive decline remains unclear. We examined the effects of these two diseases on cognitive function in elderly adults. Methods : Fifty-two elderly individuals (mean age, 69.6 ± 4.0 years) free from impairment in daily living activities participated in this study. Apnea/hypopnea index (AHI) and minimum oxygen saturation (SpO2 ) were assessed using a portable home monitoring device. We evaluated excessive daytime sleepiness with the Epworth sleepiness scale (ESS). Cognitive performance was assessed using the Wisconsin card sorting test (WCST), continuous performance test-Identical pairs (CPT-IP), and N -back task. Hypertension and diabetes mellitus were evaluated via questionnaire and blood pressure value. Results : The WCST category achievement was significantly lower in participants with minimum SpO2 <90% than those with minimum SpO2 ≥90%. The percentage of correct answer on the 0- and 1-back tasks was significantly lower in the hypertensives than normotensives. Minimum SpO2 was correlated with category achievement on the WCST. Multiple regression analysis including age, sex, body mass index, AHI, minimum SpO2, ESS, hypertension, and diabetes mellitus revealed that hypertension was the most significant factor for percentage correct answers on the 0- and 1-back tasks. There were no significant correlations between body mass index, ESS or diabetes mellitus and the parameters of WCST, CPT-IP, or N -back tasks. Conclusion : In elderly adults, nocturnal hypoxia and hypertension had a negative effect on cognitive function.